Multiphoton microscopy analysis of extracellular collagen I network formation by mesenchymal stem cells. - Vielreicher, Martin; Gellner, Monika; Rottensteiner, Ulrike; Horch, Raymund E.; Arkudas, Andreas; Friedrich, Oliver (Journal of Tissue Engineering and Regenerative Medicine, 2015)
Collagen I is the major fibrous extracellular component of bone responsible for its ultimate tensile strength. In tissue engineering, one of the most important challenges for tissue formation is to get cells interconnected via a strong and functional extracellular matrix (ECM), mimicking as closely as possible the natural ECM geometry. Still missing in tissue engineering are: (a) a versatile, high-resolution and non-invasive approach to evaluate and quantify different aspects of ECM development within engineered biomimetic scaffolds online; and (b) deeper insights into the mechanism whereby cellular matrix production is enhanced in 3D cell-scaffold composites, putatively via enhanced focal adhesion linkage, over the 2D setting. In this study, we developed sensitive morphometric detection methods for collagen I-producing and bone-forming mesenchymal stem cells (MSCs), based on multiphoton second harmonic generation (SHG) microscopy, and used those techniques to compare collagen I production capabilities in 2D- and 3D-arranged cells. We found that stimulating cells with 1% serum in the presence of ascorbic acid is superior to other medium conditions tested, including classical osteogenic medium. In contrast to conventional 2D culture, having MSCs packed closely in a 3D environment presumably stimulates cells to produce strong and complex collagen I networks with defined network structures (visible in SHG images) and improves collagen production. Copyright © 2015 John Wiley & Sons, Lt